Detection of the HBB: c.393T>G Mutation in Two Patients with Hypochromic Microcytic Anemia. (4th May 2021) - Zhao, Qiang; Zhao, Su-Min; Zhang, Xue; Chen, Shi-Ping; Sun, Jun; Peng, Zhi-Yu; Sun, Yan; Fan, Chuang; Xing, Xiao-Dan; Li, Rong
Abstract: A novel mutation, HBB : c.393T>G on the HBB gene, was detected in two hypochromic microcytic anemia patients from Yulin, in the Guangxi Province of the People's Republic of China (PRC), by next-generation sequencing (NGS). It is a nonsense mutation causing a stop codon at amino acid 131 in exon 3 of the HBB gene. It was found in a heterozygous state in two patients who both presented severe anemia during pregnancy and moderate anemia before pregnancy; Hb A2 levels were slightly increased (more than 4.0%) in both patients. It was also detected in the father of one of the patients. This mutation was pathogenic, and caused the dominant thalassemia-like phenotypes in the two patients.